Embedded system for face identification based on IRIS detection - Ahmad Nasir B. Che Rosli
This research describes the design and implementation of an Embedded System for Biometric Identification based on Iris Detection (BIOI2D). It is based on single board computer (SBC) and utilizing GNU/Linux operating system (OS) which allows the use of open source resources such as libraries, kernels drivers and GNU C compiler in developing and implementing this system.